Is this the end of the OPEC cartel? - John Abraham Godson (Comparative Economic Research. Central and Eastern Europe, 2009)
In looking at various circumstances surrounding the OPEC and the present economic crisis, one can come to a conclusion that this is the end of OPEC. This hypothesis could be supported by such factors as, falling OPEC share in the oil market, President Barack Obama's new energy policy for the United States, depleting oil reserves and the increasing worries about environmental protection. Despite these factors, it seems that the most possible scenario would be the continued strong influence of OPEC on oil prices, albeit weakened. The above hypothesis is supported by fluctuation in oil prices, rising oil demands in emerging economies like China, the dominating influence of the automobile lobby, the negative effect of bio-fuel on agriculture and finally, the underdeveloped nature of many developing countries, which in turn mean dependent on oil for years to come.
Keywords: 330